Retinal biosynthesis in fungi: characterization of the carotenoid oxygenase CarX from Fusarium fujikuroi - Prado-Cabrero, Alfonso; Scherzinger, Daniel; Avalos, Javier; Al-Babili, Salim (American Society for Microbiology, 2007)
Thecargene cluster of the ascomyceteFusarium fujikuroiencodes two enzymes responsible for torulene biosynthesis (CarRA and CarB), an opsin-like protein (CarO), and a putative carotenoid cleaving enzyme (CarX). It was presumed that CarX catalyzes the formation of the major carotenoid inF. fujikuroi, neurosporaxanthin, a cleavage product of torulene. However, targeted deletion ofcarXdid not impede neurosporaxanthin biosynthesis. On the contrary, ΔcarXmutants showed a significant increase in the total carotenoid content, indicating an involvement of CarX in the regulation of the pathway. In this work, we investigated the enzymatic activity of CarX. The expression of the enzyme in β-carotene-accumulatingEscherichia colicells led to the formation of the opsin chromophore retinal. The identity of the product was proven by high-performance liquid chromatography and gas chromatography-mass spectrometry. Subsequent in vitro assays with heterologously expressed and purified CarX confirmed its β-carotene-cleaving activity and revealed its capability to produce retinal also from other substrates, such as γ-carotene, torulene, and β-apo-8′-carotenal. Our data indicate that the occurrence of at least one β-ionone ring in the substrate is required for the cleavage reaction and that the cleavage site is determined by the distance to the β-ionone ring. CarX represents the first retinal-synthesizing enzyme reported in the fungal kingdom so far. It seems likely that the formed retinal is involved in the regulation of the carotenoid biosynthetic pathway via a negative feedback mechanism.